Juridical Review of Trademark Disputes in Indonesia: Case Study of the Trademark "Buddha To Buddha Bv" in Supreme Court Decision Number 1014k/Pdt.Sus-HKI/2016 - Mia Novita Sari; Taufiq Nugroho (Proceeding International Conference Restructuring and Transforming Law, 2023)
Brands play an important role in the business world, which is related to the rapid growth of the trade sector and even unites the business world as a single market. Even so, what happened in this area was not as anticipated by Law no. 15 of 2001 which has been modified into Law no. 20 of 2016 No. 3, namely that there are still many violations and disputes found. This writing applies a normative juridical approach. The type of research used is descriptive research. The data used is secondary data in the form of primary legal data, secondary legal data and tertiary legal data. The results of this research are that Utami Silver violates Article 76 and can be charged under Article 91 of the Trademark Law no. 15 of 2001 because Utami Silver markets jewelry with similar products. Through Buddha to Buddha By.